Gauging Risks for Deflation - Decressin, Jorg.; Laxton, Douglas (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses deflation risks and policy options. The paper highlights that slumping collateral values have exacerbated the credit crunch, and monetary policy has lost effectiveness in stabilizing output. A model-based analysis for the G3 economies (United States, euro area, and Japan) also suggests that, on the assumption that the financial distress is gradually resolved, the most likely outcome is that the global economy will stay clear of sustained deflation. However, if financial sector problems are not remedied or further shocks add to current stresses, there is a significant probability of more negative deflationary outcomes, with a deeper and more prolonged recession. The chapter underscores the crucial role of financial sector policies in remedying deflationary pressures directly and indirectly, by enhancing the effectiveness of monetary and fiscal policies. Monetary policy can help in some areas; however, supportive fiscal policies are likely to be needed to prevent a deflationary episode becoming entrenched. Monetary policy measures include operating in a broad range of financial markets to relieve credit rationing, and to lower risk spreads and term premiums. Finally, to reinforce long-run inflation expectations, central bank communications should emphasize the commitment to return inflation to objectives with all due speed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet